EFFICIENT USE OF FUEL AND ENERGY RESOURCES IN GEORGIA’S ENERGY POLICY - CHOMAKHIDZE, Demur (CENTRAL ASIA AND THE CAUCASUS, 2008)
Energy saving is one of today’s most urgent problems, and it is particularly acute in Georgia. The republic is not rich in energy resources, so in order to satisfy its economy’s demand for them, a large amount of energy is imported. This includes the entire volume of natural gas consumed, most of the oil and petroleum products, and a large percentage of electricity. What is more, Georgia far from uses its energy resources rationally; in particular, there is frequently a noticeable lag in the country’s energy efficiency indices behind similar parameters of developed countries. During the years of Soviet power, an average of almost 900 million rubles in energy resources was expended in Georgia’s material production per year. These expenditures were particularly high in industry—this sector accounted for 71% of all the expenditures in the material production sphere. The expenditures of energy resources were high in the ferrous metallurgy, chemical, and petrochemical industries. Whereas an average of 15.7 kopeks per ruble of pure product was spent in industry, this index reached 16.2 kopeks in ferrous metallurgy and almost 18 kopeks in the building material sector. These expenditures were relatively small in agriculture and construction, which shows the low level of energy supply in these industries. Research has shown that at this stage of development, the value of Georgia’s energy resources noticeably exceeded the role of labor productivity. In particular, each percent of fuel and energy resources saved in ferrous metallurgy was more significant (1.3-fold) than the percentage of increase in labor productivity. Estimates show that in 1988 an increase in labor productivity in this industry by 1% made it possible to obtain 815,000 rubles in pure product, while a drop in the energy-output ratio by 1% made it possible to save 1,069,000 rubles, or 31.2% more.1 The importance of energy resource saving increased even more during Georgia’s independence. This was promoted by the fact that the country’s economy became dependent mainly on the import of energy resources. Consequently, whereas in 1988 the value of a drop in the product energy-output ratio was higher than the value of an increase in labor productivity by 31.2%, as early as 2000, this index amounted to 76.2%. This index increases even more if production is expanded. It has been proven that the value of fuel and energy resource saving as a source of the republic’s economic growth increases as production expands and intensifies.